KINERJA KARYAWAN PADA PT. BUSSAN AUTO FINANCE DI KOTA PALU - Farista, Gita (Katalogis, 2017)
This study aimed to determine how the employee performance at PT Bussan Auto Finance in Palu City. This study used descriptive qualitative approach, for it was describing, explaining, and interpreting data in detail relating to the employee performance at PT Bussan Auto Finance in Palu City. This study used field research, for it was carried out in the field to obtain data or information directly from the informants. The main performance theories used as references were (1) Quality, (2) Quantity, (3) Timeliness, (4) Effectivity, and (5) Autonomy. The data collection techniques were observation, interview, and documentation. The data analysis technique used was Sugiyonoâ€™s Interactive Model, comprising data reduction, data presentation, data validation, and conclusion. Based on the results, it could be concluded that the employee performance at PT Bussan Auto Finance in Palu City had been good enough, but there were some things that needed to be fixed to make the employee performance better. Based on the indicators used to assess the performance, just the timeliness aspect that was unmet by the employees of Â PT Bussan Auto Finance, for there were still some employees who were often not in-time in carrying out their tasks or procrastinated for other reasons.